Study of dynamic behaviour of recession curves. Issue 3 (21st November 2012) - Biswal, Basudev; Nagesh Kumar, D.
Abstract Since Brutsaert and Neiber (1977), recession curves are widely used to analyse subsurface systems of river basins by expressing − dQ/dt as a function of Q, which typically take a power law form: − dQ/dt = kQα, where Q is the discharge at a basin outlet at time t. Traditionally recession flows are modelled by single reservoir models that assume a unique relationship between − dQ/dt and Q for a basin. However, recent observations indicate that − dQ/dt ‐ Q relationship of a basin varies greatly across recession events, indicating the limitation of such models. In this study, the dynamic relationship between − dQ/dt and Q of a basin is investigated through the geomorphological recession flow model which models recession flows by considering the temporal evolution of its active drainage network (the part of the stream network of the basin draining water at time t). Two primary factors responsible for the dynamic relationship are identified: (i) degree of aquifer recharge (ii) spatial variation of rainfall. Degree of aquifer recharge, which is likely to be controlled by (effective) rainfall patterns, influences the power law coefficient, k. It is found that k has correlation with past average streamflow, which confirms the notion that dynamic − dQ/dt ‐ Q relationship is caused by the degree of aquifer recharge. Spatial variation of rainfall is found to have control on both the exponent, α, and the power law coefficient, k. It is noticed that that even with same α and k, recession curves can be different, possibly due to their different (recession) peak values. This may also happen due to spatial variation of rainfall. Copyright © 2012 John Wiley & Sons, Ltd.